A new diminutive euphyllophyte from the Middle Devonian of West Junggar, Xinjiang, China and its evolutionary implications. Issue 4 (2nd October 2017) - Xu, Hong-He; Wang, Yao; Tang, Peng; Wang, Yi
Abstract : Xu, H.-H., Wang, Y., Tang, P. & Wang, Y., May 2017. A new diminutive euphyllophyte from the Middle Devonian of West Junggar, Xinjiang, China and its evolutionary implications. Alcheringa 41, 524–531. ISSN 0311-5518. A diminutive euphyllophyte, Douaphyton levigata gen. et sp. nov., is described from the upper Middle Devonian (Givetian) Hujiersite Formation of West Junggar, Xinjiang, China. The plant consists of more than three orders of axis branching, each axis being less than 2 mm wide. The second-order axes are short, laterally and alternately attached to the main axis. The third-order axes are paired and anisotomously divided, bearing the vegetative appendages or the fertile units. The fertile unit consists of a short recurved axis giving off up to four short pedicels along one side, each of which bears one to four pairs of terminal sporangia. Douaphyton has a three-dimensional branching system that has an intermediate form in the evolutionary context of euphyllophytes and lignophytes. It is also proposed that complex branching developed in multiple groups in the Middle Devonian. * Hong - He Xu [ hhxu@nigpas.ac.cn ], Yao Wang [ yaowang@nigpas.ac.cn ], Peng Tang [ pengtang@nigpas.ac.cn ], Yi Wang [ yiwang@nigpas.ac.cn ] State Key Laboratory of Palaeobiology and Stratigraphy, Nanjing Institute of Geology and Palaeontology, Chinese Academy of Sciences, Nanjing 210, 008, PR China. Yao Wang [ yaowang@nigpas.ac.cn ] University of Science and Technology of China. 96 Jinzhai Road, Hefei, Anhui Province, 230, 026, PR China.